2012
DOI: 10.1007/s12539-012-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

Stability and sustained oscillations in a ventricular cardiomyocyte model

Abstract: The Luo-Rudy I model, describing the electrophysiology of a ventricular cardiomyocyte, is associated with an 8-dimensional discontinuous dynamical system with logarithmic and exponential non-linearities depending on 15 parameters. The associated stationary problem was reduced to a nonlinear system in only two unknowns, the transmembrane potential V and the intracellular calcium concentration [Ca]( i ). By numerical approaches appropriate to bifurcation problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It should be noted that this study well corresponds to a certain line of research in recent years where the set of primary structure-derived features [31,32] or integral physico-chemical indices of proteins [33] have been used to predict the values of kinetic constants for particular enzymes.…”
Section: Discussionmentioning
confidence: 88%
“…It should be noted that this study well corresponds to a certain line of research in recent years where the set of primary structure-derived features [31,32] or integral physico-chemical indices of proteins [33] have been used to predict the values of kinetic constants for particular enzymes.…”
Section: Discussionmentioning
confidence: 88%
“…There is considerable experimental support and a solid theoretical background justifying this method of external current injection to suppress spontaneous rhythmic firing. Thus, previous studies based on dynamic system analysis and bifurcation theory methods applied to various models of sinoatrial or ventricular CMs, [42][43][44][45][46][47] taking a constant externally applied current as parameter and assessing its influence over a wide range of values, have shown distinct intervals of stable dynamic equilibrium at a steady V m or stable limit cycles representing sustained oscillations, that is, spontaneous pace-making. The transitions between these regimes occur at Hopf bifurcation points in the parameter space of the model.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane current system of the K05 model includes I Ca,L, IKr, IKs, 4-aminopyridinesensitive transient outward current (Ito), Na ϩ channel current (INa), inward-rectifier K ϩ channel current (IK1), background Na ϩ (INab) and Ca 2ϩ (ICab) currents, INaK, INCX, and Ca 2ϩ pump current (IpCa). Time-dependent changes in the membrane potential (Vm) are described by the equation, dV m ⁄ dt ϭ I stim Ϫ ͑ICaL ϩ I Kr ϩ I Ks ϩ I to ϩ I Na ϩ I K1 ϩ I Nab ϩ I Cab ϩ I NaK ϩ I NCX ϩ I pCa͒ (1) where Istim represents the stimulus current (in pA/pF). The O11 model further incorporates the Ca 2ϩ activated and background Cl Ϫ currents.…”
Section: Mathematical Models For Human Ventricular Myocytesmentioning
confidence: 99%
“…Tran et al (60) also explored the dynamical mechanisms of EAD formation with particular focus on the roles of I CaL and I Ks by utilizing the "slow-fast decomposition analysis" (14) in which a bifurcation diagram for the subsystem consisting of fast variables was constructed as a function of the slow variable (activation gating variable for I Ks ) regarded as a parameter for the fast subsystem. Furthermore, bifurcation analyses have been used for elucidating how individual components contribute to normal pacemaking in SAN cells (18, 27, 30 -33, 36), generation of abnormal oscillations or biological pacemaker activity in ventricular myocytes (1,5,8,28,29,62), and EADs in ventricular myocytes (1,5,15,53,54). These theoretical studies have clearly demonstrated the significance of bifurcation analyses for general understanding and systematic description of the dynamical mechanisms of normal and abnormal oscillatory behaviors.…”
Section: Significance Of Theoretical Study Using Bifurcation Analysismentioning
confidence: 99%